2017
DOI: 10.18295/squmj.2016.17.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practice and Self-Efficacy in Evidence-Based Practice among Midwives in East Iran

Abstract: Objectives:The successful implementation of evidence-based practice (EBP) can lead to appropriate and effective midwifery care during pregnancy, childbirth and in the postnatal period. However, levels of knowledge and confidence in one's ability to apply EBP are related to its effective implementation. This study aimed to investigate levels of knowledge, practice of and self-efficacy towards the use of EBP among midwives in East Iran. Methods: This cross-sectional study took place between January and February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 27 publications
8
60
0
2
Order By: Relevance
“…Their elevated level of competency self-efficacy is positively matching with their high satisfaction level about the clinical learning environment which includes: educational methodology in clinical training, instructor coaching, nursing staff supervision, peer relationship, client's communication, routine care rules, and academic grading. [1,44,45] It is essential to determine all factors that parallel and enhance nursing students' competency self-efficacy because strong competency self-efficacy is the hope of any nursing program, Medical-Surgical Nursing and Nursing Education in general. This positive correlation is expected and is a perfect sign for all our nursing students plus it is supporting the study hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their elevated level of competency self-efficacy is positively matching with their high satisfaction level about the clinical learning environment which includes: educational methodology in clinical training, instructor coaching, nursing staff supervision, peer relationship, client's communication, routine care rules, and academic grading. [1,44,45] It is essential to determine all factors that parallel and enhance nursing students' competency self-efficacy because strong competency self-efficacy is the hope of any nursing program, Medical-Surgical Nursing and Nursing Education in general. This positive correlation is expected and is a perfect sign for all our nursing students plus it is supporting the study hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the elevated level of satisfaction about clinical learning environment and high competency self-efficacy are harmonizing with nursing students' academic success. [36,45] The current research variables should be considered and encouraged among nursing students by appropriate educational planning for major clinical courses like Medical-Surgical Nursing. Clinical instructors ought to be aware by and investigate these variables and prepare clinical placement with innovative teaching approaches to increase its levels with undergraduates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many healthcare professionals still decide that clinical intervention is based on traditional practices, assumptions, personal experiences and individual beliefs and skills (Azmoude, Farkhondeh, Ahour, & Kabirian, 2017). Therefore, the students of the Ners program should learn and practice the implementation of Evidencebased Practice (EBP) during their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The self-e cacy of the nursing staff will directly affect the practice toward the signing of the DNR by the family members of the terminal patients. Many previous studies have demonstrated that self-e cacy was correlated with practice [32,33]. The main reason is that self-e cacy can improve nurses' professional practice behaviors and make them feel con dent to deliver the appropriate, timely and compassionate care [33,34].…”
Section: Path Modeling Of Knowledge Attitude and Practicementioning
confidence: 99%